INDUCED SUPERCONDUCTIVITY IN TETRAGONAL YBA2CU3O6 BY INCORPORATION OF CA - Liu, R; Cooper, J; Loram, J; Zhou, W; Lo, W; Edwards, P; Liang, W; Chen, L (1990)
The effects of the substitution of Y3+ by Ca2+ in semiconducting, tetragonal YBa2Cu3O6+δ (δ=0.10+0.01) were studied by electrical resistivity, X-ray diffraction (XRD), energy dispersive X-ray spectrometry (EDS), selected area electron diffraction (SAED) and heat capacity measurements. The maximum Tc (20K) was found for 25-30% Ca incorporation in the YBa2Cu3O6.10 compound; we find that this is also the maximum solubility limit for Ca doping. SAED patterns are consistent with disorder between the Ca and Y ions along the crystal c axis. The specific heat anomaly around 23K was observed with Δ(Tc)/Tc ∼ 2 mJ/g.at K2 and γ(0) ∼ 1.3 mJ/g.at K2. © 1990.